2011
DOI: 10.1111/j.1532-7795.2011.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Youth Organizers as Young Adults: Their Commitments and Contributions

Abstract: Nationally, youth organizing programs are growing in popularity. Although research has found positive short‐term effects associated with participation, little work has examined longer‐term implications. This study explores how alumni from one organizing group describe its influence on their subsequent developmental trajectories. Their descriptions highlight perceived effects in academic, professional, relational, and sociopolitical arenas. Although most respondents remain committed to the issues they came to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…Recent studies have described how YO groups actively engage young people in addressing social issues through political campaigns (Clay 2012;Conner et al 2013;Ferman 2012;Gordon 2010;Gordon and Taft 2011;Kwon 2013;). Analyses of survey data gathered from youth in California indicate that YO alumni exhibit a greater likelihood of participation in early adulthood than young people from similar backgrounds, thus offering support for research hypothesizing that these groups catalyze future civic and political engagement among marginalized youth (Conner 2011;Rogers et al 2012). This study fills a gap in the literature by examining patterns of civic and political participation of YO alumni members.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have described how YO groups actively engage young people in addressing social issues through political campaigns (Clay 2012;Conner et al 2013;Ferman 2012;Gordon 2010;Gordon and Taft 2011;Kwon 2013;). Analyses of survey data gathered from youth in California indicate that YO alumni exhibit a greater likelihood of participation in early adulthood than young people from similar backgrounds, thus offering support for research hypothesizing that these groups catalyze future civic and political engagement among marginalized youth (Conner 2011;Rogers et al 2012). This study fills a gap in the literature by examining patterns of civic and political participation of YO alumni members.…”
Section: Discussionmentioning
confidence: 98%
“…Future research should seek to further confirm the current findings and investigate the processes by which adolescent volunteering may affect school completion. It is possible that adolescent volunteering may enhance areas that include self-organisation, work skills, community support, and career aspirations (Conner, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Watts and Guessous () integrated both categories of outcomes into a sociopolitical development (SPD) theoretical framework for understanding the relationship between sociopolitical learning experiences in youth organizing and SPD outcomes, including sustained commitments to youth organizing group causes and career decision‐making. Academic and professional decision‐making have emerged as particularly important SPD indicators for alumni transitioning to adulthood, with youth organizing experiences influencing socially‐oriented career choices (Conner, ). Beyond youth organizing groups, Diemer and colleagues found that sociopolitical development, and specifically critical consciousness, influenced vocational and career development in marginalized youth (Diemer & Blustein, ; Diemer et al., ).…”
Section: Youth Civic Engagement In the Usmentioning
confidence: 99%
“…A series of in‐depth, phenomenologically‐based interviews were conducted with former participants and adult leaders of TASH about what it meant to participate in the program. Because TASH alumni in the study sample chose socially‐oriented careers (Conner, ), we focused on their career decisions. Beyond serving as an SPD indicator, socially‐oriented careers are an important way youth organizing groups can build capacity for social change through sustained, formal commitments of alumni.…”
Section: Youth Organizing For Comprehensive Sexual Health Educationmentioning
confidence: 99%